The Relationship Between SpO2/FiO2 Ratio to Community Acquired Pneumonia Patient Outcomes at Kolonel Abunjani Bangko General Hospital - Lindra, Derallah A; Sari, Oktriga A. (Indonesian Society of Respirology (ISR), 2024)
Background: Acute lower respiratory tract infection causes high morbidity and mortality, which can be found in the form of pneumonia. Community acquired pneumonia (CAP) severe pneumonia can lead to acute respiratory distress. To diagnose acute respiratory disorders, namely Acute Lung Injury (ALI) and Acute Respiratory Stress Syndrome (ARDS), the ratio PaO2/FiO2 is used. This requires invasive action by taking an arterial blood sample, which is expensive and not available in all health facilities. An alternative is pulse oximetry, which measures the SpO2/FiO2 ratio and is available in health facilities. It is inexpensive and non-invasive. This study aims to determine the relationship between SpO2 and FiO2 with the outcome of community pneumonia patients at Kolonel Abunjani Bangko Hospital. Method: The study design was a retrospective descriptive cross-sectional design. The research subjects were a total sampling of medical record data from inpatients with community acquired pneumonia for the period January-December 2022. The study variables included gender, age, SpO2/FiO2 ratio, and outcomes of pneumonia patients. Univariate and bivariate statistical tests were used to analyze the data. Results: In this study, there were 43 subjects who met the inclusion criteria. The distribution of inpatient community acquired pneumonia patients, especially in the gender was mostly male (67.4%), the highest age was 56–65 years and >65 years (both 37.2%), the median SpO2 was 94% (36-99%), the median SpO2/FiO2 ratio was 447 (171-471%), the highest outcomes were alive patients (36 patients). The ratio of SpO2/FiO2 >316 was the majority (33 patients). Based on the relationship between the SpO2/FiO2 ratio and the outcome of CAP with alive outcome was a SpO2/FiO2 ratio >236 was more numerous than SpO2/FiO2 ratio <236 with value of P=0.0005. Conclusion: There is a significant relationship between the SpO2/FiO2 ratio and the outcome of community acquired pneumonia patients at Kolonel Abundjani Hospital Bangko.